Effects of belt speed, pressure and grit size on the sanding of pinus elliottii wood - Alves, Manoel Cléber de Sampaio [UNESP]; Santiago, Luiz Fernando Frezzatti [UNESP]; Gonçalves, Marcos Tadeu Tiburcio [UNESP]; Valarelli, Ivaldo de Domênico [UNESP]; Varasquim, Francisco Mateus Faria de Almeida (UFLA - Universidade Federal de Lavras, 2015)
The present paper aims to evaluate the influence of the factors (belt speed, pressure and grit size) on the output parameters (temperature and surface roughness) for Pinus elliottii wood sanding, processed parallel to the fibers. Three levels of belt speed, three levels of pressure and four levels of grit size were employed, with six replicates for each process, totaling 216 observations. The experiment conducted under a randomized complete block design (RCBD). The results were analyzed employing the analysis of variance (ANOVA) with 5% of significance level. Only grit sizes were significant to different temperature levels. The same outcome was observed for roughness, where only grits sizes were significant. No interaction between the pressure and belt speed factors were observed for all the results analyzed.

Neste trabalho, objetivou-se observar o efeito dos fatores de entrada (velocidade, pressão e granulometrias de lixa) sobre as variáveis de saída (temperatura e rugosidade) no processo de lixamento plano do Pinus elliottii, processados paralelo às fibras. Foram utilizadas três velocidades, três pressões, quatro granulometrias de lixa com seis repetições para cada combinação, totalizando 216 tratamentos. O experimento foi planejado para um delineamento em blocos completamente aleatorizados (DBC). Os resultados foram analisados por meio de uma análise de variância (ANOVA) com nível de significância de 5%. Para a temperatura, observou-se que somente a granulometria de lixa teve uma influência significativa no aquecimento do sistema. Da mesma forma, a apenas a granulometria de lixa influenciou significativamente na rugosidade. Não foi observada interação entre os fatores pressão e velocidade para todos os resultados analisados.
Efeitos da velocidade, pressão e granulometria de lixa no lixamento da madeira de pinus elliottii
Keywords: Surface roughness; Temperature; Surface quality; Rugosidade; Temperatura; Qualidade superficial